Effect of Ascorbic Acid on Methylphenidate Induced Decreased Spermatogenesis in Albino Rats - Sadia Iqbal; Uzma Hameed; Muhammad Kamran; Lubna Faisal; Sara Moeen; Nasarul Huda (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Objectives: This study aimed to evaluate the anti-oxidative potential of ascorbic acid on methylphenidate induced decreased spermatogenesis and decreased testosterone levels in male Albino rats. Methods: This experimental study was performed on twelve-week-old Albino male rats selected through randomized sampling technique divided into three groups. Only healthy male rats of the same age and weighing between 180 to 200 gms were included, and any rat was appearing sick or had less weight than 180gms and aged less than 12 weeks were excluded. Control group A received 2 ml of normal saline for 50 days. Group B was given 2mg/day methylphenidate per oral for 50 days, and Group C received 2mg /day methylphenidate for 50 days, then ascorbic acid 50mg/day for 10 days. After 60 days, rats were dissected, testes were removed and histologically examined for spermatogenesis by Johnson's scoring, and blood samples were collected to evaluate testosterone levels. Results: On histological examination, the testes of animals of Group B showed a statistically significant decrease in Johnson's score (p-value < 0.001) with disruption of germinal epithelium and absence of mature sperms. These findings were associated with reduced levels of serum testosterone in this group. Administration of Ascorbic acid (AA) to group C showed statistically improved Johnson score and testosterone levels compared to group B. Conclusion: It has been concluded that administering Ascorbic Acid can improve decreased spermatogenesis and serum testosterone levels induced by methylphenidater